Climate Change in South Africa: Is there a disproportionate effect on poorer municipalities? - Motselebane, Itheheleng Imelda (University of the Witwatersrand, Johannesburg, 2024)
Climate change represents a profound and escalating challenge, disproportionately burdening the world's most vulnerable populations. The complex relationship between poverty and climate change is increasingly recognized, however, much of the existing research has concentrated on national or global scales, often overlooking the detailed, specific effects on smaller, more localized areas, such as individual municipalities within a country. This study seeks to bridge this gap by focusing on the municipal level in South Africa, a country marked by stark socio-economic inequalities and pronounced climate vulnerabilities. Utilizing a panel dataset from 234 municipalities, based on the 2011 municipal boundaries, this research employs a fixed-effects model to examine how climate shocks influence poverty dynamics across different socio-economic contexts. The findings reveal a significant divergence in the impact of climate shocks, with the poorest municipalities experiencing a markedly higher increase in poverty rates compared to their wealthier counterparts. This heightened vulnerability underscores the limited adaptive capacity of these communities, exacerbated by their dependence on climate-sensitive sectors and a lack of diversified economic opportunities. The findings underscore the importance of spatially differentiated climate adaptation strategies that are not only responsive to the immediate needs of the most vulnerable but also address the underlying structural inequalities that perpetuate their susceptibility to climate-induced economic shocks. Moreover, this research contributes to the broader discourse on climate justice, offering critical insights into the mechanisms through which climate change amplifies existing socio-economic disparities. The implications extend globally, providing a foundation for policy interventions that prioritize the protection and empowerment of the most disadvantaged communities in the face of an increasingly volatile climate.
A research report submitted in fulfillment of the requirements for the Master of Commerce (Economics/Economic Science), In the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Climate Change; Poverty; Municipalities; Climate Shock; Climate shocks; SDG-13: Climate action